2004
DOI: 10.1088/1475-7516/2004/10/012
|View full text |Cite
|
Sign up to set email alerts
|

Gödel-type universes and the Landau problem

Abstract: We point out a close relation between a family of Gödel-type solutions of 3+1 General Relativity and the Landau problem in S 2 , R 2 and H 2 ; in particular, the classical geodesics correspond to Larmor orbits in the Landau problem. We discuss the extent of this relation, by analyzing the solutions of the Klein-Gordon equation in these backgrounds. For the R 2 case, this relation was independently noticed in hep-th/0306148. Guided by the analogy with the Landau problem, we speculate on the possible holographic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
94
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(106 citation statements)
references
References 49 publications
(121 reference statements)
10
94
0
Order By: Relevance
“…Note that this dynamics in the presence of the confining potential due to the Klein-Gordon oscillator reinforces the characteristics of the quantum dynamics observed in this Gödel-type spacetime [59][60][61], which are characterized by the similarity with the Landau problem for a charged particle on a surface exposed to a uniform magnetic field. Based on this analogy, Druker et al [59] have suggested the picture of a holographic description for a single chronologically safe region. In the same paper they have conjectured that this discussion can be extended for a 4 + 1-dimensonal Gödel solution.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Note that this dynamics in the presence of the confining potential due to the Klein-Gordon oscillator reinforces the characteristics of the quantum dynamics observed in this Gödel-type spacetime [59][60][61], which are characterized by the similarity with the Landau problem for a charged particle on a surface exposed to a uniform magnetic field. Based on this analogy, Druker et al [59] have suggested the picture of a holographic description for a single chronologically safe region. In the same paper they have conjectured that this discussion can be extended for a 4 + 1-dimensonal Gödel solution.…”
Section: Discussionsupporting
confidence: 76%
“…One of these theories was developed by Gödel in the 1950s for an universe with rigid rotation characterized by a term in the metric and with a curvature source known as a Weyssenhoff-Raabe fluid [56,57]. Some studies of the quantum dynamics in this spacetime were carried out for (3 + 1)-dimensional spacetimes [58][59][60]. In this section we consider a cosmic dispiration in a flat Gödel solution or SomRaychaudhuri solution in Kaluza-Klein theory.…”
Section: Kg Oscillator In Cosmic Dislocation In Som-raychaudhuri Spacmentioning
confidence: 99%
“…This expression is analogous to the vector potential that yields a uniform magnetic field in the z-direction. An interesting property of this type of metric is that the geodesics for this spacetime are circles, which have a physical description similar to Larmor orbits for an electron that moves in a perpendicular magnetic field [8,9]. This analogy also arises from the point of view of quantum mechanics, where the quantum dynamics of scalar and spinorial quantum particles in this spacetime is an analogue of the Landau levels, as observed in Refs.…”
Section: Linear Confinement In the Som-raychaudhuri Spacetime With A mentioning
confidence: 80%
“…[7], the first study of this problem was made, where the KleinGordon and Dirac equations in the Gödel-type spacetimes with positive and negative curvatures were investigated, and also in a flat Gödel-type spacetime. Further, the investigation of the relationship between the quantum dynamics of the scalar quantum particle in background of general relativity with Gödel solutions and the Landau levels in the flat, spherical and hyperbolic spaces was performed by Drukker et al [8]. They analyzed the similarity between the spectrum of the energy of a scalar quantum particle in these class of Gödel-type spacetimes and the Landau levels in curved backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…As an application of Gödel-type problems in the relativistic studied we can indicate that gravitational coupling of Klein-Gordon and Dirac fields to matter vorticity and spacetime torsion, in the context of Einstein-Cartan theory with a e-mail: hha1349@gmail.com b e-mail: mimip44@naver.net c e-mail: soroushzrg@gmail.com d e-mail: hadisobhani8637@gmail.com a Gödel-type metric, have been done by Figueiredo [7]. A close relation was seen between a family of Gödel-type solutions of 3+1 general relativity and the Landau problem, as reported by Drukker [8]. The quantum dynamics of a scalar particle in three spaces whose metrics are described by different classes of Gödel solutions, with a cosmic string passing through the spaces has been studied [9].…”
Section: Introductionmentioning
confidence: 93%